Given the system of equations, match the following items.
2x - y = 0
x + y= -3

Question

Asked 2/26/2015 10:52:09 AM

Updated 3/1/2015 6:50:30 AM

2 Answers/Comments

This conversation has been flagged as incorrect.

Flagged by yeswey [3/1/2015 6:49:04 AM]

(x + y = 0) * (-2) =

-2x - 2y = 0;

(2x - y = -3) + (-2x - 2y = 0) =

-3y = -3;

y = -3/-3; y = 1;

x + 1 = 0;

x = -1

Question

Asked 2/26/2015 10:52:09 AM

Updated 3/1/2015 6:50:30 AM

2 Answers/Comments

This conversation has been flagged as incorrect.

Flagged by yeswey [3/1/2015 6:49:04 AM]

Rating

3

2x - y = 0

x + y = -3

adding up equations the result is:

3x = -3

x = -3/3 = -1

y = 2x = 2(-1) = -2

The solution set for the system 2x - y = 0 x + y= -3 is (-1, -2)

x + y = -3

adding up equations the result is:

3x = -3

x = -3/3 = -1

y = 2x = 2(-1) = -2

The solution set for the system 2x - y = 0 x + y= -3 is (-1, -2)

Added 3/1/2015 6:48:52 AM

This answer has been confirmed as correct and helpful.

Confirmed by jeifunk [3/1/2015 7:29:58 AM]

3

(x + 5 < 4)

x < 4 - 5

x < -1;

(x - 3 > -6)

x > -6 + 3

x > -3

The solution for the inequality system (x + 5 < 4) (x - 3 > -6) is {x | -3 < x < -1}

x < 4 - 5

x < -1;

(x - 3 > -6)

x > -6 + 3

x > -3

The solution for the inequality system (x + 5 < 4) (x - 3 > -6) is {x | -3 < x < -1}

Added 3/1/2015 6:50:30 AM

This answer has been confirmed as correct and helpful.

Confirmed by jeifunk [3/1/2015 7:32:03 AM]

29,328,425

questions answered

There are no comments.